2020
DOI: 10.1016/s0140-6736(20)30848-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high-dose 24-h infusion of tranexamic acid on death and thromboembolic events in patients with acute gastrointestinal bleeding (HALT-IT): an international randomised, double-blind, placebo-controlled trial

Abstract: Background Tranexamic acid reduces surgical bleeding and reduces death due to bleeding in patients with trauma. Meta-analyses of small trials show that tranexamic acid might decrease deaths from gastrointestinal bleeding. We aimed to assess the effects of tranexamic acid in patients with gastrointestinal bleeding. Methods We did an international, multicentre, randomised, placebo-controlled trial in 164 hospitals in 15 countries. Patients were enrolled if the responsible clinician was uncertain whether to use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(120 citation statements)
references
References 18 publications
1
107
0
7
Order By: Relevance
“…In contrast to our study, these trials did not use active Duplex screening for TE, thereby potentially underreporting TE events. However, our results are consistent with the HALT-IT study, an RCT on TXA use in 12,000 adults with gastrointestinal bleeding that reported an increase in TE when TXA is used in this population (59).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to our study, these trials did not use active Duplex screening for TE, thereby potentially underreporting TE events. However, our results are consistent with the HALT-IT study, an RCT on TXA use in 12,000 adults with gastrointestinal bleeding that reported an increase in TE when TXA is used in this population (59).…”
Section: Discussionsupporting
confidence: 90%
“…It should also be noted that the recent HALT-IT trial was included in this study even though it assessed the effects of TXA on GI bleeding in general but not isolated to upper GI sources. The reasoning behind this was the fact that the study reported that over 89% of those included in the study were deemed to have an upper GI bleed and thus it should be translatable to our study [ 12 ]. Also, this study is the largest and most recent study of its kind assessing this question and so it was deemed appropriate to include it with the above proviso acknowledged.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included are detailed in Table 2 . A total of 8 studies were included in this systematic review [ 12 – 19 ]. The number of patients included in the studies ranged from a low of 47 to a high of 12009.…”
Section: Resultsmentioning
confidence: 99%
“…Twum‐Barimah et al recently addressed the importance of tranexamic acid in acute gastrointestinal bleeding in their systematic review 1 . The HALT‐IT trial reported contradictory results ‐ that is, tranexamic acid confers no additional survival benefit and is associated with increased harm 2 . Karadaş et al found no statistically significant difference in mortality between patients with gastrointestinal bleeding who received tranexamic acid or placebo 3 .…”
Section: Figurementioning
confidence: 99%
“…Forest plot of tranexamic acid vs placebo on mortality and overall outcome summary, including 24‐hour mortality, 72‐hour mortality, 1‐month mortality and end of follow‐up mortality. ✶ HALT‐IT trial reported 28‐day mortality, which was also included in our 1‐month mortality analysis 2 . † Two studies published in 2020 were added in addition to those included in the meta‐analysis by Erica Twum‐Barimah et al 2,3 ‡ Two studies published in 2020 and one study whose reported outcome was missed were added in addition to those included in the meta‐analysis by Erica Twum‐Barimah et al 2,3,5 § One study published in 2020 and one study whose reported outcome was missed were added in addition to those included in the meta‐analysis by Erica Twum‐Barimah et al 2,6 …”
Section: Figurementioning
confidence: 99%